A cell hybridization-based method of generating recombinant rabbit monoclonal antibodies for detecting cytokines - Yu Peng; Chun'e Zhang; Minyan Deng; Haijuan Jiang; Huishu Huang; Yue Li; Weiping Lai; Yu-pin Lin; Jun Yu (BioTechniques, 2023)
Recombinant rabbit monoclonal antibodies (rabbit rAbs) have shown promise in various biomedical fields. However, it is challenging and costly to generate rabbit rAbs using traditional techniques. Here we describe a convenient and cost-effective method. Using this method, we generated rabbit rAbs against mouse soluble IL-6 receptor α with affinities in the range of 10-9 to 10-12 M. The presented method is suitable for industrial and academic scientists looking to customize rabbit rAbs for their research.